2022
DOI: 10.7759/cureus.24620
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Mesenteric Ossification With Trilineage Hematopoiesis

Abstract: Heterotopic ossification (HO) histologically refers to extraskeletal bone formation in non-ossifying tissues, most commonly noted in the extremities, buttocks, abdominal wall, and hip joints. HO developing in the mesentery (heterotopic mesenteric ossification, HMO) is very rare, with fewer than 100 cases reported in the literature. It usually occurs in adult male patients with a history of repeated abdominal trauma. So far, only two cases of HMO have been reported with the development of hematopoietic bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…There are limited research studies investigating HSCs’ involvement in HO, and those that are available have provided conflicting evidence of HSC involvement. Several clinical case studies have shown evidence of trilineage hematopoiesis in excised tHO bone [ 131 , 142 , 143 , 144 , 145 ]. Although these case studies indicate the presence and involvement of HSCs in the HO site, there is insufficient evidence to indicate that these cells are involved in the process of osteogenesis in HO formation.…”
Section: Progenitor Cell Populations In Tho and Fopmentioning
confidence: 99%
“…There are limited research studies investigating HSCs’ involvement in HO, and those that are available have provided conflicting evidence of HSC involvement. Several clinical case studies have shown evidence of trilineage hematopoiesis in excised tHO bone [ 131 , 142 , 143 , 144 , 145 ]. Although these case studies indicate the presence and involvement of HSCs in the HO site, there is insufficient evidence to indicate that these cells are involved in the process of osteogenesis in HO formation.…”
Section: Progenitor Cell Populations In Tho and Fopmentioning
confidence: 99%